Entrepreneurship Orientation and Holistic Marketing Mix in Creating Competitive Advantages Bumdes - I Gusti Ketut Adi Winata; Ni Made Wulan Sari Sanjaya; I Gusti Made Oka Astana (Institut Pariwisata dan Bisnis Internasional, 2020)
Bumdes is a company in a village that needs to establish a competitive advantage. This is because there are many similar businesses throughout Buleleng district. This study aims to understand the relationship between entrepreneurial orientation and holistic marketing mix as a source of competitive advantage for BUMDes Buleleng Regency. The data analysis technique used in this study is the SEM GeSCA method. The results showed entrepreneurial orientation has no direct influence on competitive advantage, but the indirect effect through a holistic marketing mix. The competitive advantage of Bumdes in Buleleng district can be created through the development of an entrepreneurial orientation which is translated into marketing activities.